A comparison of tabun-inhibited rat brain acetylcholinesterase reactivation by three oximes (HI-6, obidoxime, and K048) in vivo detected by biochemical and histochemical techniques - Bajgar, Jiri; Hajek, Petr; Zdarova, Jana Karasova; Kassa, Jiri; Paseka, Antonin; Slizova, Dasa; Krs, Otakar; Kuca, Kamil; Jun, Daniel; Fusek, Josef; Capek, Lukas (Journal of enzyme inhibition and medicinal chemistry, 2010)
Tabun belongs to the most toxic nerve agents. Its mechanism of action is based on acetylcholinesterase (AChE) inhibition at the peripheral and central nervous systems. Therapeutic countermeasures comprise administration of atropine with cholinesterase reactivators able to reactivate the inhibited enzyme. Reactivation of AChE is determined mostly biochemically without specification of different brain structures. Histochemical determination allows a fine search for different structures but is performed mostly without quantitative evaluation. In rats intoxicated with tabun and treated with a combination of atropine and HI-6, obidoxime, or new oxime K048, AChE activities in different brain structures were determined using biochemical and quantitative histochemical methods. Inhibition of AChE following untreated tabun intoxication was different in the various brain structures, having the highest degree in the frontal cortex and reticular formation and lowest in the basal ganglia and substantia nigra. Treatment resulted in an increase of AChE activity detected by both methods. The highest increase was observed in the frontal cortex. This reactivation was increased in the order HI-6 < K048 < obidoxime; however, this order was not uniform for all brain parts studied. A correlation between AChE activity detected by histochemical and biochemical methods was demonstrated. The results suggest that for the mechanism of action of the nerve agent tabun, reactivation in various parts of the brain is not of the same physiological importance. AChE activity in the pontomedullar area and frontal cortex seems to be the most important for the therapeutic effect of the reactivators. HI-6 was not a good reactivator for the treatment of tabun intoxication.
Keywords: pyridinové sloučeniny; Reticular Formation; oximy; mozek; Organophosphates; Pyridinium Compounds; Frontal Lobe; Oximes; LD50; chemické bojové látky; čelní lalok; Female; Organ Specificity; krysa rodu Rattus; zvířata; GPI-Linked Proteins; potkani Wistar; retikulární formace; cholinesterasové inhibitory; organofosfáty; ženské pohlaví; Rats, Wistar; Atropine; Brain; Acetylcholinesterase; atropin; reaktivátory cholinesterasy; Lethal Dose 50; Cholinesterase Reactivators; Rats; Animals; Chemical Warfare Agents; GPI-vázané proteiny; Obidoxime Chloride; obidoxim chlorid; orgánová specificita; acetylcholinesterasa; Cholinesterase Inhibitors